2014
DOI: 10.1093/jpepsy/jsu023
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Comprehensive Behavioral Family Lifestyle Interventions Addressing Pediatric Obesity

Abstract: CBFLIs demonstrated efficacy for improving weight outcomes in youths who are overweight or obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
207
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(222 citation statements)
references
References 55 publications
8
207
2
5
Order By: Relevance
“…However, in the current study, the number of treatment contacts, number of treatment months, and number of visits with a pediatrician were particularly important, such that larger effect sizes were associated with more treatment contacts, longer duration of treatment, and greater involvement from a pediatrician. This finding is consistent with Janicke et al (2014), who reported that larger effect sizes were associated with longer treatment (duration in months) and more treatment sessions. It is left to future studies to determine whether the impact of treatment duration and number of contacts differs depending on who is delivering the intervention or on the background and level of training of the interventionist.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the current study, the number of treatment contacts, number of treatment months, and number of visits with a pediatrician were particularly important, such that larger effect sizes were associated with more treatment contacts, longer duration of treatment, and greater involvement from a pediatrician. This finding is consistent with Janicke et al (2014), who reported that larger effect sizes were associated with longer treatment (duration in months) and more treatment sessions. It is left to future studies to determine whether the impact of treatment duration and number of contacts differs depending on who is delivering the intervention or on the background and level of training of the interventionist.…”
Section: Discussionsupporting
confidence: 91%
“…4,5 Two other metaanalyses have reported larger intervention differences of 0.31 and 0.47. 4,6 However, Ho et al 4 showed that study duration was important with much larger effects in shorter studies than those lasting .6 months (0.31 vs 0.09 BMI z score units, respectively). Janicke et al 6 included studies in adolescents and showed that age was a significant moderator, with greater effects in older children.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 However, Ho et al 4 showed that study duration was important with much larger effects in shorter studies than those lasting .6 months (0.31 vs 0.09 BMI z score units, respectively). Janicke et al 6 included studies in adolescents and showed that age was a significant moderator, with greater effects in older children. 6 Direct comparisons are also complicated given that each metaanalysis was examining related but subtly different types of interventions, from educational approaches 5 to comprehensive lifestyle interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations